Effect of arterial pressure measurement location on pulse contour stroke volume estimation, during a rapid change in hemodynamic state. Issue 27 (2018) - Balmer, Joel; Pretty, Christopher; Davidson, Shaun; Desaive, Thomas; Habran, Simon; Chase, J. Geoffrey
Abstract: Continuous cardiac output monitors are becoming more common in clinical settings to assess cardiac performance. Pulse contour analysis is a common method employed by commercial devices to estimate patient hemodynamics from a pressure waveform and relate it to volume. The main issue with current devices, is they can perform poorly during and after a significant hemodynamic event. An existing pulse contour analysis method, under ideal experimental conditions, demonstrated the ability to track changes in stroke volume (SV) using a measure of pulse wave velocity (PWV). In this study, the existing method's ability to estimate SV was tested during vena cava occlusions (VCO), a worst case, rapid transient hemodynamic change. Additionally, the method's sensitivity to the location of the arterial pressure waveform measurement was also assessed, by comparing SV estimates from aortic and iliac pressures, to SV measured by admittance catheter in the ventricle. Results show the model accurately tracks changes in SV as a result of the occlusion, a significant improvement over current commercially available devices. Bland-Altman analysis showed no significant improvement in SV estimation when using aortic pressure compared to the iliac pressure waveform, with mean bias of -2.11ml and 0.13ml, respectively. This is a desirable result, as more distal arterial pressure measurement locations increase the clinical feasibility of the method.